The Silence Of Responsibility: Rethinking The “S” In The ESG Amid Humanitarian Injustice - Ahmad Fadzil, Ahmad Syahmi; Zainoddin, Amir Imran; Hakim Ab Jalal, Muhammad Zulqarnain; Raja Zainalabidin, Raja Amir Ashraf (Journal of Islamic, Social, Economics and Development, 2025)
The “S” in ESG meant to represent corporate social responsibility, often lacks moral clarity, especially during humanitarian crises. Many corporations adopt socially responsible language while remaining silent or complicit in the face of atrocities such as war, forced displacement, or apartheid. The humanitarian catastrophe unfolding in Palestine, marked by mass suffering and structural violence, exposes the ethical limitations of corporate ESG commitments and the absence of decisive moral action. This paper argues that the “S” in ESG must evolve beyond symbolic gestures to embrace humanitarian accountability. The first research objective is to validate whether there is an increasing trend in academic discourse aimed at improving ESG. The second is to propose stronger elements for the “S” that are ethically grounded and sensitive to humanitarian injustice. Using VOSviewer, a bibliometric analysis of 173 academic articles was conducted to map ESG research trends and identify gaps. This analysis revealed emerging concerns about ESG’s social limitations. From these insights, the paper proposes three interconnected domains—symbolic social compliance, strategic silence, and humanitarian accountability—to strengthen the ethical foundation of the “S.” Rather than replacing ESG, the paper calls for its reconstruction: repositioning corporate social responsibility as a matter of conscience and justice, not just compliance.